Reducing Procurement Lead Time For Maintenance Spare Parts At Pt Bukit Asam Tbk - Indriani, Oktavia; Handayati, Yuanita (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2026)
PT Bukit Asam Tbk (PTBA) processed 2,679 procurement requests in the first half of 2025 with 55% consist of maintenance spare parts that are essential to keep operations run smoothly and reliably contains 1,368 PR (Purchase Requisition). The focus of this study was to examine and enhance the procurement lead time for maintenance spare parts from PR is submitted until a purchase order (PO) is finalized. The research methodology combined quantitative analysis of transaction data used BPMN modeling process and simulation through Bizagi software. Additional insights were gathered through interviews and focus group discussions (FGD) with relevant stakeholders. The As-Is process simulation shows that the total procurement lead time reached 60.5 days from start to finished well beyond the company's target of 50 days. The main delays occurred during the procurement execution phase and when PO creation, largely because of repetitive procedures and approval processes that required manual intervention. To tackle these challenges the Author proposed several business solution and approach Business Process Reengineering (BPR) mentioned electronic signatures to speed up approvals, establishing umbrella contracts to eliminate redundant procurement cycles, vendor rating system and a risk dashboard implementation that provides real-time visibility into potential issues. The To-Be simulation from proposed improvements in a blended scenario where 45% of procurements adopt umbrella contracts and 55% remain under conventional methods showed results the average lead time decreased to 44.7 days which is exceed to the expected KPI target. These results indicate that combination of digital approval workflows, standardized contract arrangements and proactive risk monitoring can substantially improve how efficiently procurement operates. Furthermore, this study also demonstrates the practical value of BPR can improve procurement operations more responsive and dependable within the mining sector.